I-Learn Portal: Universiti Teknologi MARA Pahang student's e-learning continuance intention level and influences factors / Mohd Rizal Razak and Nor Zalina Ismail - Razak, Mohd Rizal; Ismail, Nor Zalina (Penerbit UiTM (UiTM Press), 2016)
Blended Learning (BL) is the teaching and learning technique implemented in Universiti Teknologi MARA (UiTM) for the past few years. BL is the approach that combines the physical classroom learning and electronic learning (e-Learning). UiTM has developed an i-Learn portal as a platform to support e-Learning activities. The users of the i-Learn portal are UiTM students and lecturers. The objectives of this study is to determine an individual usage continuance intention level for the i-Learn portal services in UiTM Pahang. Other objectives are to identify the factors that lead to the agreement or reluctance of continuity in using i-Learn portal services in UiTM. This quantitative research used questionnaire as a tool to gather information from the respondents. Decomposed technology acceptance model proposed by Juan Carlos Roca et. Al (2006) is used as an outline on questionnaire design. This model is used because it is tailored for e-Learning services characteristics. The respondents for this research are Diploma in Computer Science UiTM Pahang students that have the experience using i-Learn portal services in their studies. Most of the subjects taught for Diploma in Computer Science at UiTM Pahang implement the blended learning technique that utilized the i-Learn Portal services. The results of this research on continuance intention towards i-Learn Portal among UiTM Pahang students is undecided. The factors that lead to this result is less perceived on cognitive absorption, flaws on information quality and the system quality.